Time-restricted feeding and cognitive function in sedentary and physically active elderly individuals: Ramadan diurnal intermittent fasting as a model - Boujelbane, Mohamed Ali; Trabelsi, Khaled; Jahrami, Haitham A.; Masmoudi, Liwa; Ammar, Achraf; Khacharem, Aïmen; Boukhris, Omar; Puce, Luca; Garbarino, Sergio; Scoditti, Egeria; Khanfir, Saber; Msaad, Aymen; et al. (Frontiers in Nutrition, 2022)
Objectives This study aimed to investigate the effects of Ramadan diurnal intermittent fasting (RDIF) on cognitive performance, sleep quality, daytime sleepiness, and insomnia in physically active and sedentary elderly individuals. Methods A total of 58 participants (62.93 ± 3.99 years) were assigned to one of the following two groups: a sedentary group (control group) who observed Ramadan (n = 32) and a physically active group (n = 26) who continued to train while observing Ramadan. Participants were assessed 2 weeks before Ramadan and during the fourth week of Ramadan. On each occasion, participants completed a digital assessment of their cognitive performance and responded to the Pittsburgh sleep quality index (PSQI), the insomnia severity index (ISI) and the Epworth sleepiness scale (ESS) questionnaires to assess sleep parameters. Results Compared to before Ramadan, performance in executive function (p = 0.035), attention (p = 0.005), inhibition (p = 0.02), associative memory (p = 0.041), and recognition memory (p = 0.025) increased significantly during Ramadan in the physically active group. For the sedentary group, associative learning performance decreased (p = 0.041), whilst performances in the remaining domains remained unchanged during Ramadan. Global PSQI, ISI, and ESS scores indicated both groups suffered from poor sleep quality and excessive daytime sleepiness, with significantly higher negative effects of RDIF observed in the sedentary group. Conclusion Older adults who continue to train at least three times per week during Ramadan may improve their cognitive performance, despite the impairment of sleep quality. Future studies in older adults during Ramadan including objective measures of sleep (e.g., polysomnography, actigraphy) and brain function (e.g., functional magnetic resonance imaging) are warranted.